2015
DOI: 10.1016/j.chom.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging of Gut Microbiota Spatial Organization

Abstract: Summary Genomic technologies have significantly advanced our understanding of the composition and diversity of host-associated microbial populations. However, their spatial organization and functional interactions relative to the host have been more challenging to study. Here we present a pipeline for the assessment of intestinal microbiota localization within immunofluorescence images of fixed gut cross-sections that includes a flexible software package, BacSpace, for high-throughput quantification of microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
379
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(399 citation statements)
references
References 33 publications
17
379
1
2
Order By: Relevance
“…These differences could be explained by AMP being differentially expressed in physiological conditions along the SI (66), and thus respond differentially with respect to microbiota modulation. Moreover, it was recently shown that elimination of the microbiota-accessible carbohydrates, which are highly represented in dietary fibers and used as substrate by intestinal bacteria, induces a shift of the microbiota toward mucus-consuming bacteria and consequently results in closer proximity of bacteria with the epithelium (67). However, no data are actually available concerning the impact on the spatial distribution of microbiota of missing microbiotaaccessible carbohydrates in the small intestine.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These differences could be explained by AMP being differentially expressed in physiological conditions along the SI (66), and thus respond differentially with respect to microbiota modulation. Moreover, it was recently shown that elimination of the microbiota-accessible carbohydrates, which are highly represented in dietary fibers and used as substrate by intestinal bacteria, induces a shift of the microbiota toward mucus-consuming bacteria and consequently results in closer proximity of bacteria with the epithelium (67). However, no data are actually available concerning the impact on the spatial distribution of microbiota of missing microbiotaaccessible carbohydrates in the small intestine.…”
Section: Discussionmentioning
confidence: 91%
“…In our model collapse of the mucus barrier could favor the emergence of such bacteria able to use it as substrate, or diet-mediated increase in this species may further participate in the alteration of the mucus barrier (67,73). Interestingly, the treatment of HF-fed mice with rosiglitazone was able to restore the spatial distribution of the ileal microbiota but not the composition compared with SD-fed mice, indicating that biochemical parameters, such as electrolytes and mucus releases, play pivotal roles in maintaining microbiota at a distance from the epithelium, but diet composition determine the microbiota composition (67). Other bacterial species were affected under HF diet, such as SFB.…”
Section: Discussionmentioning
confidence: 99%
“…Mucus acts to protect the gut epithelium from mechanical stress, to lubricate the intestine to ease transit of digested material, and to prevent the translocation of harmful substances. A study comparing a standard rodent diet (fiber from wheat, corn, and oats comprising 4.3% of the diet by weight) with a diet devoid of any fiber showed that mice fed the fiber-deficient diet had a thinner mucus layer, thus allowing microbes to come in closer proximity to the gut epithelium (61). Without sufficient amounts of DF in the gut, bacteria may degrade the host mucus layer in order to provide themselves with the substrates necessary to survive, thus breaking down one of the host's physical barriers.…”
Section: Impact Of Df On the Gut The Gatekeeper Of The Bodymentioning
confidence: 99%
“…Some biofilms are beneficial to human health, for example as part of the healthy gut and skin microbiota (5,6) or in wastewater treatment systems (7). Other biofilms, however, cause serious problems in oral hygiene, chronic infections, and prosthetic contamination (8)(9)(10) and act as fouling agents in industrial flow systems (11).…”
mentioning
confidence: 99%